2018
DOI: 10.1002/2017jd027782
|View full text |Cite
|
Sign up to set email alerts
|

Simulations of the Boreal Winter Upper Mesosphere and Lower Thermosphere With Meteorological Specifications in SD‐WACCM‐X

Abstract: We investigate the benefit of high‐altitude nudging in simulations of the structure and short‐term variability of the upper mesosphere and lower thermosphere (UMLT) dynamical meteorology during boreal winter, specifically around the time of the January 2009 sudden stratospheric warming. We compare simulations using the Specified Dynamics, Whole Atmosphere Community Climate Model, extended version, nudged using atmospheric specifications generated by the Navy Operational Global Atmospheric Prediction System, Ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 65 publications
(128 reference statements)
0
18
0
Order By: Relevance
“…Smith‐Johnsen et al () showed better agreement with observations when D region chemistry was added to the Whole Atmosphere Community Climate Model (WACCM) but the NO underestimate persisted between 90 and 110 km. Recent studies have shown that either constraining the model up to 90 km or assimilating mesospheric data improves the representation of the EPP IE (Pedatella, Liu, et al, ; Sassi et al, ; Siskind et al, ). In the Antarctic, Hendrickx et al () show EPP‐NO x underestimates despite MLT descent rates in WACCM that agree with observations.…”
Section: Introductionmentioning
confidence: 99%
“…Smith‐Johnsen et al () showed better agreement with observations when D region chemistry was added to the Whole Atmosphere Community Climate Model (WACCM) but the NO underestimate persisted between 90 and 110 km. Recent studies have shown that either constraining the model up to 90 km or assimilating mesospheric data improves the representation of the EPP IE (Pedatella, Liu, et al, ; Sassi et al, ; Siskind et al, ). In the Antarctic, Hendrickx et al () show EPP‐NO x underestimates despite MLT descent rates in WACCM that agree with observations.…”
Section: Introductionmentioning
confidence: 99%
“…Global climate models (GCMs) underestimate these effects (Funke et al, ; Hendrickx et al, ; Holt et al, ; Orsolini et al, ; Randall et al, ; Sheese et al, ), and optimum performance occurs when the models are constrained by observations to mesospheric heights (Pedatella et al, ; Sassi et al, ; Siskind et al, ). Indeed, GCMs often simulate a reversal of the winter westerlies above 70–80 km that is not consistent with observations (e.g., Smith, , see their Figure 2).…”
Section: Introductionmentioning
confidence: 99%
“…They indicated that better analysis of the mesosphere requires assimilation of the mesospheric 150 observational data. Similar discussion was made by Sassi et al (2018) using the Specified Dynamics (SD)-WACCM, in which a nudging method was implemented. The reality of the analysis highly depends on the model's performance in the MLT region.…”
mentioning
confidence: 88%